Electronic-Tindak Lanjut Tensiku (E-TITENKU) Intervention Model Development for The Prevention of Coronary Heart Disease - Sidik Awaludin; Galih Noor Alivian; Aprilia Kartikasari; Dwi Novitasari (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2022)
Coronary Heart Disease is still the leading cause of death globally. Therefore, primary prevention efforts are needed to reduce morbidity and mortality from Coronary Heart Disease. The era of the industrial revolution demands the use of digital information technology in solving every problem, including in the field of nursing. Electronic Tindak Lanjut Tensiku (e-TITENKU) is a nursing intervention application designed to increase knowledge of coronary heart disease prevention through controlling blood pressure and direct nursing interventions if the user has hypertension according to their level. The purpose of this study was to develop an e-TITENKU intervention model for the prevention of coronary heart disease. The design of this research is research and model development, where researchers develop models and applications based on web and smartphones based on theoretical studies, for smartphone application operations. application using Analysis, Design, Development, Implementation, and Evaluation (ADDIE) approach. The results of the research on the e-TITENKU model have been compiled and the results of 2 expert tests obtained Kappa test results of 0.85. This model can be used easily to categorize the level of hypertension, providing nursing interventions to reduce hypertension according to the level. Keywords: coronary heart disease; hypertension; nursing intervention model; smartphonePengembangan Model Intervensi Electronic-Tindak Lanjut Tensiku (E-TITENKU) untuk Pencegahan Penyakit Jantung KoronerABSTRAK Penyakit jantung koroner masih menjadi penyakit penyebab kematian tertinggi di tingkat global. sehingga diperlukan upaya pencegahan primer untuk mengurangi kesakitan dan kematian akibat penyakit jantung koroner. Era revolusi industri menuntut penggunaan teknologi informasi digital dalam menyelesaikan setiap permasalahan termasuk dibidang keperawatan. Electronic Tindak Lanjut Tensiku (e-TITENKU) merupakan aplikasi intervensi keperawatan yang disusun untuk meningkatkan pengetahuan pencegahan penyakit jantung koroner melalui pengontrolan tekanan darah dan intervensi keperawatan secara langsung apabila pengguna mengalami hipertensi sesuai levelnya. Tujuan penelitian ini untuk mengembangkan model intervensi e-TITENKU untuk pencegahan penyakit jantung koroner. Desain penelitian ini yaitu research and model development yaitu peneliti melakukan pengembangan model dan aplikasi berbasis web dan smartphone berdasarkan kajian teori, untuk operasional aplikasi smartphone. aplikasi dengan menggunakan pendekatan Analysis, Design, Development, Implementation, dan Evaluation (ADDIE). Hasil penelitian model e-TITENKU telah disusun dan hasil uji 2 oarang pakar diperoleh hasil uji Kappa 0.85. Model ini dapat digunakan secara mudah untuk mengkategorikan level hipertensi, pemberian intervensi keperawatan untuk menurunkan hipertensi sesuai levelnya. Kata kunci: hipertensi; jantung coroner; model intervensi keperawatan; smartphone